Bipolar disorder - Reiser, Robert P; Thompson, Larry W; Johnson, Sheri L; Suppes, Trisha (Advances in psychotherapy--evidence-based practice, 2016)
"This extensively updated new edition of the acclaimed book in the Advances in Psychotherapy series integrates empirical research from the last 10 years to provide clear and up-to-date guidance on the assessment and effective treatment of bipolar disorder. The expert authors, a team of psychotherapists and medical practitioners, begin by describing the main features of bipolar disorder based on DSM-5 and ICD-10 criteria. Current theories and models are described, along with decision trees for evaluating the best treatment options. They then outline a systematic, integrated, and empirically supported treatment approach involving structured, directive therapy that is collaborative and client-centered as well as clear medication management guidelines. Special considerations, including managing suicide risk, substance misuse, and medication nonadherence, are also addressed. This compact, stand-alone resource aims to help psychotherapists, psychologists, medical and psychiatric practitioners, and nurses deliver the highest standards of care for people with bipolar disorder."--